Suitability of coastal saline soils of Gopalapuram, Nellore for shrimp farming - Gupta, B P; Muralidhar, M; Joseph, K O; Krishnani, K K (Indian Journal of Fisheries, 2011)
Soil samples collected from various depths, at different sites of Gopalapuram farmarea, Andhra Pradesh were analysed for their physico-chemical characteristicsfor the suitability of brackishwater aquaculture. The soils are poor in organiccarbon (0.23 to 0.5 %). Average pH values ranged from 5.2 to 8.4. Low pH valuesare associated with higher values of iron and lower values of CaCOg. Texturalclass of soil varies from sandy loam to sandy clay loam. Sand/silt ratio valuesranged from 4,0 to 10.3. Organic carbon, available nitrogen and phosphorus contentof soil decreased with increasing depth of soil sampling. Iron content of soils waspositively correlated with increasing depth and negatively correlated with pH andCaCOg content. Some important satistical correlations among soil characteristicswere also worked out. The farm area was suitable for brackishwater aquaculturewith suitable management of moderate limitation properties of the soils.